LEARNING IN STUDENTS WITH SPECIAL EDUCATIONAL NEEDS FROM AN INNOVATIVE PERSPECTIVE - Author; Lubis Carmita Zambrano Montes; Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The teaching work is built and innovated every day, the teacher develops different activities within his professional role, assumes commitments and provides open solutions to educational diversity. The research aims to analyze innovative perspectives to strengthen teaching in students with special educational needs. The application of active methodologies and pedagogical tools in learning supports the educational practice of the teacher in the construction of new ways of teaching, strengthening the authentic and meaningful learning of the students, in this study deductive and inductive methods were used, to make an analysis from the general to the particular and vice versa, with a qualitative approach, a bibliographic review of scientific articles from journals was carried out in reliable databases; in addition to Google Scholar, providing reliable and scientific information, together with a historical-logical procedure, to contextualize the research. It was obtained as a result that the innovative perspectives project horizons of radical changes in the educational field through the planning, organization, and implementation of school activities with the help of the various support manuals provided by the Ministry of Education, with methodological strategies and pedagogical skills to intervene in the classroom in a positive way.